2021
DOI: 10.1177/14613484211063095
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and control of hybrid MR seat damper and whole body vibration evaluation for bus drivers

Abstract: This paper describes the design, simulation, and performance evaluation of hybrid MR damper on quarter bus semi-active seat suspension coupled with human biodynamic model. Also, the whole body vibration (WBV) exposures were evaluated based on the international standard ISO 2631 (1997), and its parameters were used to measure the level of discomfort for bus drivers. The hybrid MR damper was proposed to enhance the damping force within low current supplied and achieve a fail-soft capability in case of electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, such EVs face some issues when in use on the road [15]. Major problems associated with the EVs while riding are short-range [18], higher weight [19], and bulkiness of the energy storage systems such as battery packs hence lowering the utility space [20], whole-body vibrations [21,22], torque ripple [23], and torsion between traction motor and driveline [24]. Any successful attempt made in overcoming or minimizing the aforesaid deficiencies would result in improving the efficiency and performance of futuristic EVs.…”
Section: Ice Motorcyclementioning
confidence: 99%
“…However, such EVs face some issues when in use on the road [15]. Major problems associated with the EVs while riding are short-range [18], higher weight [19], and bulkiness of the energy storage systems such as battery packs hence lowering the utility space [20], whole-body vibrations [21,22], torque ripple [23], and torsion between traction motor and driveline [24]. Any successful attempt made in overcoming or minimizing the aforesaid deficiencies would result in improving the efficiency and performance of futuristic EVs.…”
Section: Ice Motorcyclementioning
confidence: 99%
“…In the random excitation test, the root mean square value of the seat acceleration is effectively reduced and the ride comfort is improved. Munyaneza Olivier et al [11] used the Skyhook controller to control the current supply of the hybrid magnetorheological damper and enhance the damping force under low current power supply. The skyhook controller improves seat comfort compared to uncontrolled conditions.…”
Section: Of 20mentioning
confidence: 99%
“…A simple structure-model of seat isolator designed by the horizontal-parallel isolator (HPI) has been studied for vehicles moving on rigid road surfaces. 3,5,6 The HPI’s design parameters were then optimized while the damping values in the HPI were also controlled for enhancing the isolation performance of the seat’s HPI. Study results showed that the vertical vibration, pitch vibration, and roll vibration of the seat were significantly improved in comparison with the use of the traditional isolator of the seat.…”
Section: Introductionmentioning
confidence: 99%